Gerald O’Collins, Revelation. Towards a Christian Interpretation of God’s Self-Revelation in Jesus Christ, Oxford University Press, Oxford 2016, ss. 247, ISBN 978-0-19-108700-3. - Bergel, Łukasz (Biblica et Patristica Thoruniensia, 2019)
Recenzja książki pt. Revelation. Towards a Christian Interpretation of God’s Self-Revelation in Jesus Christ autorstwa Geralda O’Collinsa.